Britain in the Twentieth Century - Cawood, Ian (Spotlight history., 2004)
Britain in the Twentieth Century is a new approach to teaching and learning twentieth century British history at A level. It meets the needs of teachers and students studying for today's revised AS and A2 exams. In a unique style, Britain in the Twentieth Century focuses on the key topics within the period. Each topic is then comprehensively explored to provide background, essay writing advice and examples, source work and historical skills. From 1900 to the new millennium, the key topics featured include:* Britain in a new century, 1900-1914* the First.